Accelerated start-up and granulation in polymer-enhanced UASB bioreactors treating industrial food-processing wastewater - Foong, Shiu Feng. (2008)
This study included a treatability study of the wastewater characteristics through examination of its biochemical oxygen demand (BOD), chemical oxygen demand (COD), pH, total and volatile suspended solids (TSS and VSS) and others. The possibility of accelerating the start-up time and granulation process in UASB reactors was investigated with addition of 1, 2 and 4 mg polymer/g SS in three laboratoryscale UASB reactors. Further investigation into optimising the polymer additions was investigated through adding biweekly polymer dosages into the reactors in the last phase.